Analisis Kebutuhan Tenaga Ahli Teknologi Laboratorium Medik Berdasarkan Beban Kerja di Unit Laboratorium Klinik Rumah Sakit Santa Maria Pekanbaru - Arifin, Arifin; Sjaaf, Amal Chalik (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2018)
The main challenge of the clinical laboratory unit in hospitals nowdays is making expenditures efficiency, especially human resources expenditures. On the other hand, patients and doctors normally request faster and more accurate laboratory checking results. The purpose of this study is to get proper number of medical laboratory technology experts needed based on workload in Santa Maria Pekanbaru Hospital Clinical Laboratory Unit. Research method applied is operational research with quantitative and qualitative analysis. Workload analysis was done toward the whole medical laboratory technology experts, which were 15 person, with the combination method of work sampling and daily log. The calculation of expert need was done with 3 methods: Ilyas, WISN, and the Full Time Equivalent Method. The study result is there are 18 medical laboratory technology experts needed according to Ilyas Method, 21 experts according to WISN Method, and 17 experts according to Full Time Equivalent Method. It is suggested to Santa Maria Pekanbaru Hospital to add 3 more medical laboratory technology experts.